Ethical decision making in pain management: a conceptual framework - Carvalho, A. S. (2018)
Introduction: The practice and study of pain management pose myriad ethical challenges. There is a consensual opinion that adequate management of pain is a medical obligation rooted in classical Greek practice. However, there is evidence that patients often suffer from uncontrolled and unnecessary pain. This is inconsistent with the leges artis, and its practical implications merit a bioethical analysis. Several factors have been identified as causes of uncontrolled and unnecessary pain, which deprive patients from receiving appropriate treatments that theoretically they have the right to access. Important factors include (with considerable regional, financial, and cultural differences) the following: 1) failure to identify pain as a priority in patient care; 2) failure to establish an adequate physician–patient relationship; 3) insufficient knowledge regarding adequate prescription of analgesics; 4) conflicting notions associated with druginduced risk of tolerance and fear of addiction; 5) concerns regarding “last-ditch” treatments of severe pain; and 6) failure to be accountable and equitable. Objective: The aim of this article was to establish that bioethics can serve as a framework for addressing these challenging issues and, from theoretical to practical approaches, bioethical reflection can contextualize the problem of unrelieved pain. Methods: This article is organized into three parts. First, we illustrate that pain management and its undertreatment are indeed ethical issues. The second part describes possible ethical frameworks that can be combined and integrated to better define the ethical issues in pain management. Finally, we discuss possible directions forward to improve ethical decision making in pain management. Discussion: We argue that 1) the treatment of pain is an ethical obligation, 2) health science schools, especially medical training institutions, have the duty to teach pain management in a comprehensive fashion, and 3) regulatory measures, which prevent patients from access to opioid treatment as indicated in their cases, are unethical and should be reconsidered. Conclusion: Developing an ethical framework for pain management will result in enhanced quality of care, linking the epistemic domains of pain management to their anthropological foundations, thereby making them ethically sound.